Expo ’58 en “Koning Auto” - Michel Hubert (Brussels Studies, 2008)
Whereas it took more than forty years to complete the North-South railway junction, a scant three years was necessary to change the face of the city of Brussels completely and turn it into one of the European capitals with the highest levels of car ownership. Expo ’58 had a crucial role in accelerating this movement. After explaining the circumstances that led to the “car as king” attitude in Brussels, the author wonders about the difficulties of having Brussels embrace an urban development model less dependent on the car. According to the Brussels-Capital Region’s forecasts, the entire territory concerned by the extension of the future Regional Express Rail Network will be under the overwhelming domination of the car by 2015. The prospect of the crisis situation that this will spawn is an opportunity to be seized to turn the trend around. As we approach a new bend in the technological road, only a massive investment plan in Brussels’s mass transport and the latter’s integration in a management and information system on the appropriate functional scale (the REN area) could offset the road network development plans that marked the three decades that began with Expo ’58. Such a policy cannot be waged without thinking about road traffic and parking conditions, the external costs of travelling by car, and the latter’s contribution to financing public transport. Nor will it be possible without setting up civic participation schemes. The loss of attractiveness of urban areas that have been degraded by the colossal road infrastructure projects of the past can be combated, as shown by the examples of urban regeneration carried out in Boston and Madrid.